Preliminary thermodynamic assessment for advanced-cycle marine gas turbines. - Sanchez de Leon, Luis (Cranfield University, 2014)
Nowadays, around 80% to 90% of the international trade is made by sea, and the vast majority of the large merchant ships are powered by means of low-speed two-stroke diesel engines. Currently, gas turbines have only found niche markets in certain marine applications —such as the military or fast ferries, in which reduced size, mass, noise and vibration levels of the power plant are of paramount importance—, but their capability for entering the sector of the large cargo vessels (containers, bulk carriers, etc.) remains unexplored. Main disadvantages for the gas turbines to become a viable option for powering these ships are the very high thermal efficiency and extremely low running costs that the large diesel engines actually offer. However, as long as the current trend continues, diesel power plants are likely to lose one of their major advantages —i.e. their low operating costs— due to the ongoing regulations regarding ship emissions (IMO’s MARPOL 73/78 Annex VI) and the severe reduction in the established limits for Sulphur contents in fuels for marine applications. In such a scenario, in which emissions from ships are relentlessly being cut down lower and lower, diesel engines will have to move to more expensive distillate fuels, likely equalising their fuel prices with the gas-turbine-based power plants and, therefore, opening a potential window for the latter to enter the market. Hence, the main question posed at this point would be: given the expected equalisation in fuel prices between the gas turbines and the diesel engines, is it possible to devise an advanced gas turbine-based power plant that could outcompete the low-speed two-stroke diesel engines as prime mover for marine commercial applications? Working with this hypothesis of fuel prices no longer posing a competitive advantage for diesel engines, and making the simplifying assumption (as a sensible first-order approach to the problem) that the targeted marine applications spend most of their time at cruise speed —i.e. with the prime mover operating very close to its design point—the overall thermal efficiency at nominal conditions will be the main driving parameter to carry out the comparative assessment among the different power plants considered herein. The aim of this research is, thus, to investigate if and which sort of advanced gas-turbine-based power plants could be able to deliver thermal efficiencies high enough to outperform modern diesel engines in this regard, at least at design-point operation. The research comprises two markedly different phases: in phase one of this project, a wide range of candidate gas-turbine-based power plants are proposed and parametrically optimised for maximum thermal efficiency at design point, so that their relative merits against one another can be established consistently and the few most promising cycles can be downselected for further research; in phase two, these few downselected candidates will be physically characterised, carrying out preliminary size and mass estimations of the whole prime mover, along with some acquisition costs assessment. The results presented in this thesis demonstrate the great potential of certain advanced thermodynamic cycles, still based on a gas turbine as the core of the power plant, to achieve outstanding levels of performance at design point, effectively outcompeting the diesels in this regard by a good margin, potentially between 5 and 10 percentage points. In particular, the evaporative gas turbines and the combined-cycle power plants were the most promising candidates analysed, yielding thermal efficiencies at design point in the surrounds of 60%–65%. As it will be shown, these advanced gas turbine-based power plants are, in general, comparable in size to the diesel engines, but can mean huge reductions in the overall uninstalled dry mass of the prime mover. Despite the acquisition costs being significantly higher for the gas turbines, the great potential savings in fuel consumption — because of the higher thermal efficiencies— could make out of these advanced gas-turbine-based power plants a cost-effective solution in the long run for powering large merchant ships.
Keywords: Gas tubine; power plant; cruise speed; advanced; thermal efficiency; large merchant ships